2018
DOI: 10.1177/1178221817752678
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Those With Long-Term Substance Use Disorders Stop Abusing Substances? A Qualitative Study

Abstract: Although a significant proportion of adults recover from substance use disorders (SUDs), little is known about how they reach this turning point or why they stop using. The purpose of the study was to explore the factors that influence reasoning and decision making about quitting substance use after a long-term SUD. Semistructured interviews were conducted with 18 participants, each of whom had been diagnosed with a SUD and had been abstinent for at least 5 years. A resource group of peer consultants in long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 42 publications
2
30
0
Order By: Relevance
“…7,11,47 The importance of the sibling relationship to SUD recovery has not been described previously, although the role of a close family member has been mentioned in other studies in the contexts of both mental illness and SUD. 9,45 SUD treatment providers should involve clients' networks to a greater extent when designing new treatment approaches. They should invite significant others, family, and friends of the client to treatment programs, in the interest of promoting and prolonging positive relationships relevant to establishing sobriety.…”
Section: Discussionmentioning
confidence: 99%
“…7,11,47 The importance of the sibling relationship to SUD recovery has not been described previously, although the role of a close family member has been mentioned in other studies in the contexts of both mental illness and SUD. 9,45 SUD treatment providers should involve clients' networks to a greater extent when designing new treatment approaches. They should invite significant others, family, and friends of the client to treatment programs, in the interest of promoting and prolonging positive relationships relevant to establishing sobriety.…”
Section: Discussionmentioning
confidence: 99%
“…Inspiration to do so came from care providers or other persons who were engaged in their change process and who extended a significant support by offering a hopeful and persevering attitude. The importance of supportive staff attitudes has been highlighted in other studies with former heroin users (Brunelle et al 2015;Pettersen et al 2018;Weiss et al 2014) To maintain the decision to refrain from heroin use the possibility to gain a new social context in which they could be active, keeping busy and counted upon was crucial. To be able to redefine the identity and to restore one's spoiled identity was also something described as decisive for quitting heroin in a Greek study (Fotopoulou 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In one study, participants with illegal drug use identified factors that were perceived to help increase motivation, including humility and patience among clinical staff (Brunelle et al 2015). It may also be helpful for both patient and provider to explore the individual's reasons for seeking help (Pettersen et al 2018). Studies on overcoming addiction have generally been conducted within treatment samples.…”
Section: Introductionmentioning
confidence: 99%
“…This also appears in first-person experiences of co-occurring disorders [ 21 , 34 36 ]. Importantly, there seems to be considerable individual variation in how substance use relates to recovery among people with co-occurring disorders [ 37 ], as well as in reasons for quitting substance use [ 38 ], and a categorical total abstinence approach seems to be at odds with recovery principles of supporting each individual’s goals and interests. Further, as is reflected in team members’ descriptions in the present study, demanding total abstinence in community services may indirectly exclude citizens from services.…”
Section: Discussionmentioning
confidence: 99%